STUDY OF SWOT ANALYSIS INFORMATION SYSTEM MAIL AND LOGISTIC (MLO) WEB BASED APPLICATION - Arum Puspita Ayu; Harianto Respati; Dwi Arman Prasetya (JAREE (Journal on Advanced Research in Electrical Engineering), 2018)
Information technology becomes one of the important elements for an organization or company in realizing the effectiveness and efficiency of performance.  To create a company that has a good performance, it requiring the existence of an information system to assisting the management in taking a decision. In its implementation, the use of existing information system still encounter some obstacles during the operation. In this study, the authors used application belongs to Mail and Logistic (MLO) agenpos application. Therefore, SWOT analysis is needed to know the strengths and weakness in internal factors and to know the opportunities and threats in external factors. Choosing the right strategy can maximize the strengths and opportunities, on the other side can minimize the weaknesses and threats. Keywords: SWOT analysis, Mail and Logistic (MLO) Agenpos Application, Strategy, Internal Factors, External Factors